Peningkatan Limfosit, Monosit, dan Basofil pada Sapi Bali yang Digembalakan di Tempat Pembuangan Akhir Sampah Kota Denpasar (THE ELEVATION LEVEL OF LIMPHOCYTE, MONOCYTE, AND BASOPHIL ON BALI CATTLE GRAZING AT WASTE DISPOSAL CITY OF DENPASAR) - Ariana, I Nyoman Tirta; Oka, Anak Agung; Suranjaya, I Gede; Berata, I Ketut (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
The Bali cattles that grazing at Denpasar city waste disposal need to examined for their healthy to keep the quality of beef production. The aim of this research to determine the hematologic profile of Bali cattle was grazing at waste disposel in Denpasar. The data obtained is expected to provide an initial ekspretion of the general health-related to productivity. Studies using nine female of Bali cattle weighing 250-300 kg, aged 2-3 years. Research using quantitative methods by means of surveys and research laboratory. The research variables are Total White blood cells (WBC), lymphocytes, monocytes, basophils, and Total Red blood cell (RBC), haemoglobin (Hb), mean corpuscular volume (MCV). The result showed that the total of RBC, Hb, and MCV were still within the normal range. The other result were the average WBC: 4.8%, lymphocytes: 25.3%, Monocytes: 2.8%, and Basophils: 0.8% higher if compared to the same variable in cows were well maintained. It can be concluded that the Bali cattle grazing in the area of the landfill affected pathophysiological change in its body.